TYPES OF ERRORS IN WRITING SYLLABIC FORMATS - Vicente, Francisco (2019)
Research already available shows orthographic difficulties in a population of different levels of education, from basic to university, and in different varieties of Portuguese (cf. Abaurre, 2001; Gonçalves & Vicente, 2010; Miranda & Matzenauer, 2010; Santos, 2013; Veloso 2003; among others). The objective of the present study was to describe the types of errors in writing of different syllable formats (CV, V, CCV, CVC) by Mozambican children of Basic Education (2nd, 3rd, and 5th graders), speakers of Portuguese as L2 (second language), whose L1 (mother tongue) is Changana. To achieve this objective, through a task of picture naming, the subjects were asked to write a set of words (cf. Santos, 2013; Veloso, 2003). The words tested included syllables of different formats: V (asa), CV (faca), CCV (prato, blusa) e CVC (porta, balde, pasta). The analysis of the collected data showes that in non-branching Onsets (simple and empty) errors are rare. In the spelling of CR clusters, the deletion of C2 was the most frequent error. However, in the spelling of CL clusters, there was a balance between the deletion of C2 and vowel epenthesis. Regarding errors in the types of Codas (S, R and L), Coda deletion was the most frequent error. These results are broadly in line with the trend attested in previous studies on writing in Portuguese as a mother tongue (cf. Silva, 2015; Veloso, 2003). The preferred epenthetic vowel in the writing of Mozambican children evaluated was . However, in Portuguese Basic Education, the preferred epenthetic vowel in the spelling of branching syllable formats is <e> (cf. Lourenço-Gomes, Rodrigues & Alves, 2016; Santos, 2013; Veloso, 2003).